Shaping an Open Microbiome for Butanol Production through Process Control - Tiago Pinto; Antonio Grimalt-Alemany; Xavier Flores-Alsina; Hariklia N. Gavala; Krist V. Gernaey; Helena Junicke (Fermentation, 2022)
The growing awareness of limited resource availability has driven production systems towards greater efficiencies, and motivated the transition of wastewater treatment plants to water resource recovery facilities. Open microbiome fermentation offers a robust platform for resource recovery, due to its higher metabolic versatility, which is capable of dealing with even dilute residual liquid streams. Organic matter, e.g., fatty acids, lost in these streams can potentially be recovered into higher value chemicals such as alcohols. This study aims to shape an open microbiome towards butanol production from butyrate and hydrogen through pH control and continuous hydrogen supply. Two sets of experiments were conducted in Scott bottles (1 L) and a lab-fermenter (3 L). The open microbiome produced up to 4.4 mM butanol in 1 L bottles. More promising conversions were obtained when up-scaling to a lab-fermenter with pH control and an increased hydrogen partial pressure of 2 bar; results included a butanol concentration of 10.9 mM and an average volumetric productivity of 0.68 mmol L−1 d−1 after 16 days. This corresponds to 2.98- and 4.65-fold increases, respectively, over previously reported values. Thermodynamic calculations revealed that product formation from butyrate was unfeasible, but energetically favorable from bicarbonate present in the inoculum. For the first time, this study provides insights regarding the community structure of an open microbiome producing butanol from butyrate and hydrogen. DNA sequencing combined with 16S rRNA gene amplicon analysis showed high correlation between Mesotoga spp. and butanol formation. Microbial diversity can also explain the formation of by-products from non-butyrate carbon sources.